Evaluasi Dan Perbaikan Usability Pada Antarmuka Pengguna Website Universitas Islam Malang Menggunakan Metode Heuristic Evaluation - Esmeralda Y.A. Tambunan; Buce Trias Hanggara; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Website of the Islamic University of Malang (UNISMA) is the official website of UNISMA, which created as a center of information regarding campus profiles, lecture activities, and campus announcements. Based on the results of interviews with UNISMA and its students, there are several problems that have been experienced. This research conducted using Heuristic Evaluation method. Heuristic Evaluation is a method used to find usability problems in an interface. The evaluation in this study carried out in two stages. The first stage evaluation Is before the improvement and the second stage evaluation is after the improvement. The results of the first stage evaluation found 29 problems from each evaluator. Then a mapping was carried out which resulted in 24 problems, of which 5 problems were found by more than one evaluator and 19 problems were found by one evaluator. Furthermore, second stage performed for the improvement prototype involving the same evaluator as the first stage evaluation. The results of the second stage evaluation found 10 problems from each evaluator. Then the mapping was carried out which resulted in 7 problems, 3 problems were found by more than one evaluator and 4 problems were found by one evaluator